Behavioral variation in natural contests: integrating plasticity and personality. (20th January 2021) - Couchoux, Charline; Garant, Dany; Aubert, Maxime; Clermont, Jeanne; Réale, Denis
Abstract: Animals often interact aggressively when competing over limited resources. Aggressive decisions can be complex and may result from multiple sources of behavioral variation. The outcome of contests may be explained through contest theory and personality by considering conjointly plasticity and individual consistency. This integrative approach also allows investigating individual differences in responsiveness to environmental changes. Here, we observed multiple agonistic interactions occurring among eastern chipmunks ( Tamias striatus ) competing for food resources supplied at different distances from their burrows. Using an individual reaction norm approach, we found that the probability of winning a contest depended on an individual's intrinsic characteristics (mass and age but not sex) but was also adjusted to characteristics of its opponents. Winning a contest also depended on extrinsic environmental characteristics, such as distance to the contestants' burrows, but not the order of arrival at the feeding patch. We found consistent individual differences in the probability of winning, potentially related to differences in aggressiveness and territoriality. We also found that individuals differed in their plasticity level in response to changes in different characteristics of their social and physical environments. Plasticity, personality, and individual differences in responsiveness may thus all play a role in predicting contest outcome and in the evolution of animal contests. Abstract : Who wins the fights? Behavioral plasticity and individual consistency both drive decision-making during aggressive social interactions in eastern chipmunks. Observations of multiple aggressive interactions reveal that individuals win more when they are heavier, older, and closer to their burrow and also respond to these characteristics in their opponents. But territory owners can also lose as chipmunks show consistent tendencies to win a fight that may reflect their underlying aggressiveness and level of territoriality. Individuals also vary in their capacity to respond to a change in location or opponent.